Fault location method for multi-section hybrid lines considers velocity uncertainty - Liwei Xie; Youpeng Wang; Yang Xiao; Xiangjun Zeng; Yan Mo; Zhuo Long (International Journal of Electrical Power & Energy Systems)
Fault location accuracy of traveling wave method is constrained to the reliable traveling wave velocity. In this paper, a novel fault traveling waves location method is proposed to eliminate the effects of velocity uncertainty on hybrid lines’ fault location. The initial amplitude ratio coefficient (IARC) K is defined based on propagation characteristic analysis of initial fault traveling wave (IFTW) signals for hybrid lines, and the corresponding identification principle of fault line sections is derived from numerical relationships within different fault points’ K values. Then, taking into account the uncertainties of fault traveling wave (TW) velocity, a fault location method based on the virtual time difference is proposed. By comparing the difference value between the virtual time difference value and the real arrival time difference value of IFTW signals, the minimum difference value is defined as the objective function H. The fault location result is equal to the optimal fault distance value of the objective optimal model, so that the negative effects of velocity uncertainty are reduced. Besides, in order to search for the optimal value, a selected opposition-based grey wolf optimizer (SOGWO) is employed. Various fault scenarios are simulated, and the obtained results validate that the proposed approach is reliable for identifying fault sections and locating fault points in hybrid lines.